The role of the nursing coordinator and the leadership style in the Italian healthcare organizations - Lupo, Roberto; Lezzi, Alessia; Conte, Luana; Ingrosso, Natascia; Artioli, Giovanna; Botti, Stefano; Leone, Cosimo; Rubbi, Ivan; Carvello, Maicol; Calabrò, Antonino; Vitale, Elsa (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: The leadership of the Nursing Coordinator is essential to ensure quality care and to empower the nursing staff. To identify the leadership style used by the coordinator as nurses and the support staff perceive the leadership behaviors of the coordinator. Methods: Data were collected through an online questionnaire including the Empowering Leadership Questionnaire. Results: Positive associations were recorded between participants’ satisfaction levels and high standards of job performance (p